ETHICAL DYNAMICS IN CORPORATE GOVERNANCE: A GLOBAL PERSPECTIVE ON CORPORATE GOVERNANCE PRACTICES - Diva Aulia Ni`masari; Pinky Permata Sari; Rohmawati Kusumaningtias (PT Wahana Global Education, 2025)
This article explores the crucial role of ethics in corporate governance (CG), emphasizing that good governance is not solely about legal compliance but about embedding ethical principles into corporate decision-making for long-term sustainability. Ethical governance strengthens stakeholder trust and mitigates risks associated with corporate misconduct, as illustrated by past scandals like Enron and Volkswagen. The study examines the ethical dynamics of corporate governance on a global scale, analyzing practices, challenges, and emerging standards across diverse cultural and regulatory contexts. Drawing insights from literature reviews, international reports (OECD, World Bank, UN Global Compact), and relevant case studies, the article highlights the roles of stakeholders, the interplay between cultural norms and legal frameworks, and the impacts of globalization and digitalization on ethical governance. The findings provide actionable recommendations to enhance ethical practices in corporate governance, aiming to build resilient, transparent, and socially responsible organizations in an increasingly interconnected world.